X-ray Analysis of Biomass Wood Briquette Structure (Agricultural Engineering, 2016)
The study aims to measure the wood chips flow during the briquetting process by the X-ray image analysis. Scots pine (Pinus sylvestris L.) constituted the used feedstock that has been previously divided, according to the standard, into four (>1.0; 1.1-4.0; 4.1-8.0; 8.1-16.0 mm) groups of fraction. Examination of the X-ray image allows description of the movement of the wood fractions flow after the briquetting process. The correlations between the vertical axis and scattering plane factors were estimated. The correlation coefficient was 0.973 and was almost complete. The calculations were made for the areas of deviations (SD) and the area of scattering planes (DPS). Particular flow irregularities were determined for deviations ranges of individual groups of fractions and were (>1.0)=3.04; (1.1-4.0)=4.08; (4.1-8.0)=6.33 and (8.1-16.0)=7.33 cm2, and for scattering planes they were accordingly e (>1.0)=0.32; (1.1-4.0)=0.72; (4.1-8.0)=0.97 and (8.1-16.0)=1.29 cm2.